Impact of left atrial volume, sphericity, and fibrosis on the outcome of catheter ablation for atrial fibrillation. (6th April 2018) - den Uijl, Dennis W.; Cabanelas, Nuno; Benito, Eva M.; Figueras, Rosa; Alarcón, Francisco; Borràs, Roger; Prat, Susanna; Guasch, Eduard; Perea, Rosario; Sitges, Marta; Brugada, Josep; Berruezo, Antonio; et al.
Abstract: Introduction: To investigate the relation between left atrial (LA) volume, sphericity, and fibrotic content derived from contrast‐enhanced cardiac magnetic resonance imaging (CE‐CMR) and their impact on the outcome of catheter ablation for atrial fibrillation (AF). Methods and results: In 83 patients undergoing catheter ablation for AF, CE‐CMR was used to assess LA volume, sphericity, and fibrosis. There was a significant correlation between LA volume and sphericity (R  =  0.535, P < 0.001) and between LA volume and fibrosis (R  =  0.241, P  =  0.029). Multivariate analyses demonstrated that LA volume was the strongest independent predictor of AF recurrence after catheter ablation (1.019, P  =  0.018). Conclusion: LA volume, sphericity, and fibrosis were closely related; however, LA volume was the strongest predictor of AF recurrence after catheter ablation.